A Study on the Key Factors Affecting Speaking Fluency in Indonesian Higher Education Settings - Abdullah Kafabih; Rozanah Katrina Herda; Leong Jin Jee (Universitas Sarjanawiyata Tamansiswa, 2026)
English speaking fluency plays a crucial role in supporting students’ academic achievement and global employability. However, many learners continue to struggle with spoken English despite years of formal instruction. This study investigates key factors influencing speaking fluency among university students in the Indonesian higher education context, focusing on personal attributes, cultural and social influences, and pedagogical practices. A mixed-methods approach was used, with data collected through questionnaires from 105 students and semi-structured interviews with 10 participants. The findings indicate that psychological barriers, such as anxiety and lack of confidence, are significant obstacles to speaking fluency. Additionally, limited exposure to authentic English practice and teacher-centered pedagogical approaches contribute to the challenges faced by students. However, the study also highlights positive factors that enhance fluency, such as interactive teaching strategies, vocabulary development, and the provision of constructive feedback. These elements were found to significantly improve students’ fluency and boost their confidence in speaking. Furthermore, the study emphasizes the importance of peer interaction, supportive learning environments, and the integration of technological tools in promoting speaking proficiency. The results suggest that these factors play a critical role in developing students’ communicative competence. Based on these findings, the study offers practical recommendations for educators and policymakers, emphasizing the need for tailored interventions to address students’ specific challenges and improve their English speaking skills in the context of Indonesian higher education. Keywords: speaking fluency, psychological barriers, interactive teaching, higher education, language learning strategies.